Natural fiber modified material, preparation method and application in building insulation field
By adding hemp fibers and modified carbon to polymer foaming materials and performing hot pressing molding, the problems of insufficient strength and increased density of existing materials are solved, and better mechanical properties and thermal insulation properties are achieved.
Patent Information
- Application Number
- CN202411911973.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
In the field of building insulation, existing polymer foaming materials need to be added to improve mechanical properties due to their low strength, but this leads to an increase in density and affects application.
A natural fiber modified material is developed to improve the mechanical properties of the material by mixing hemp fibers, modified carbon, silane coupling agent, fire retardant, and waterproofing agent with polystyrene resin beads and performing hot pressing molding.
It realizes the improvement of the mechanical properties of polymer foaming materials without increasing the material density and enhances its application performance in the field of building insulation.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building thermal insulation materials, and in particular to natural fiber modified materials, preparation methods and applications in the field of building thermal insulation. Background Art
[0002] Organic polymer foam materials have various excellent properties such as light weight, heat insulation, sound insulation, shock absorption, flame retardancy, moisture resistance, etc., and are therefore widely used in product packaging and transportation, vehicle and ship manufacturing, building insulation, pipeline insulation and protection, and other fields.
[0003] Thermal insulation materials for construction are an important application field of polymer foam materials. However, since the strength of polymer foam materials is relatively low compared to inorganic materials, in many actual operations, inorganic or metal materials are added to polymer foam materials to improve the mechanical properties. However, this will greatly increase the density, affecting its application in areas such as exterior walls of high-rise buildings.
[0004] Therefore, it is necessary to develop a method that can improve the mechanical properties of polymer foam materials without much change in density. Summary of the invention
[0005] In order to solve at least one of the above technical problems and develop a polymer foam material with improved mechanical properties but little change in material density, the present application provides a natural fiber modified material, a preparation method and its application in the field of building insulation.
[0006] On the one hand, the present application provides a natural fiber modified material, which is prepared by including the following components in parts by weight:
[0007] 70-85 parts of polystyrene resin beads;
[0008] 5-10 parts of hemp fiber;
[0009] 5-12 parts of modified carbon;
[0010] Silane coupling agent 0.5-2 parts;
[0011] 5-8 parts of fire retardant;
[0012] 1 to 3 parts of waterproofing agent;
[0013] The modified carbon uses activated carbon as a raw material, the activated carbon is impregnated in quaternary ammonium salt, attapulgite is added, the mixture is stirred and evenly mixed, and the modified carbon is obtained after drying and solidification.
[0014] Optionally, the modified carbon is prepared under acidic conditions.
[0015] Optionally, in the modified carbon, the weight ratio of activated carbon, quaternary ammonium salt and attapulgite is (50-60):(5-10):(30-40).
[0016] Optionally, the particle size of the activated carbon is 0.5 to 5 mm;
[0017] And / or, the particle size of the attapulgite is 0.2 to 1 μm.
[0018] Optionally, the fire retardant is a combination of one or more of ammonium phosphate and zinc borate.
[0019] Optionally, the waterproofing agent is an organosilicon emulsion, to which polyethylene glycol 800 is added.
[0020] In a second aspect, the present application provides a method for preparing the above-mentioned natural fiber modified material, comprising the following steps:
[0021] S1. Washing, drying and cutting the hemp fibers into segments;
[0022] S2, mixing the pretreated hemp fiber in S1 with the modified carbon, the silane coupling agent, the fire retardant, the waterproof agent and the polystyrene resin beads to obtain a mixture;
[0023] S3, hot pressing the mixture in S2 to obtain a natural fiber modified material.
[0024] Optionally, the length of the hemp fiber after being cut into segments is 5 to 10 mm.
[0025] Optionally, the polystyrene resin beads in S2 are pre-foamed by heating, and then matured after being uniformly mixed with the hemp fibers pretreated in S1, the modified carbon, the silane coupling agent, the fire retardant and the waterproofing agent.
[0026] In a third aspect, the present application provides the application of the above-mentioned natural fiber modified material in the field of building insulation.
[0027] In summary, the present invention includes at least one of the following beneficial technical effects:
[0028] 1. By adding hemp fiber, the connection performance of polystyrene particles after foaming is improved, thereby improving the mechanical properties of the foamed material;
[0029] 2. By adding activated carbon and wrapping it with polystyrene, the thermal insulation and sound insulation properties can be improved through the porous characteristics of the activated carbon. Moreover, since the activated carbon is wrapped with polystyrene, it does not affect the overall fire resistance of the material. Moreover, the activated carbon is filled inside the polystyrene, which can improve the mechanical properties of the foamed material. DETAILED DESCRIPTION
[0030] The present application is further described in detail below with reference to the embodiments.
[0031] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products.
[0032] Polystyrene resin beads: purchased from Shanghai Secco Petrochemical Co., Ltd.;
[0033] Hemp fiber: purchased from Zhejiang Golden Eagle Co., Ltd.;
[0034] Activated carbon: coconut shell activated carbon is used as an example, purchased from Anhui Quanhu Activated Carbon Co., Ltd.;
[0035] Quaternary ammonium salt: cetyltrimethylammonium bromide (CTAB) is exemplified;
[0036] Silane coupling agent: γ-aminopropyltriethoxysilane (APTES) is used as an example;
[0037] Fire retardant: ammonium phosphate is used as an example;
[0038] Waterproofing agent: an organic silicon emulsion to which 2 wt % of polyethylene glycol 800 is added is used as an example.
[0040] Preparation Examples 1 to 5 are used to prepare the modified carbon in this application; the details are as follows.
[0041] Preparation Example 1
[0042] This preparation example is used to prepare modified carbon. Activated carbon is used as a raw material. 10 parts by weight of quaternary ammonium salt is added with water to prepare a solution. 50 parts by weight of activated carbon are immersed in the solution. 40 parts by weight of attapulgite are added. The mixture is stirred and mixed evenly. The modified carbon is obtained after drying and solidification.
[0043] Preparation Example 2
[0044] This preparation example is used to prepare modified carbon. Activated carbon is used as a raw material. 5 parts by weight of quaternary ammonium salt is added with water to prepare a solution. 55 parts by weight of activated carbon are immersed in the solution. 40 parts by weight of attapulgite are added. The mixture is stirred and mixed evenly. The modified carbon is obtained after drying and solidification.
[0045] Preparation Example 3
[0046] This preparation example is used to prepare modified carbon. Activated carbon is used as a raw material. 10 parts by weight of quaternary ammonium salt is added with water to prepare a solution. 55 parts by weight of activated carbon are immersed in the solution. 35 parts by weight of attapulgite are added. The mixture is stirred and mixed evenly. The modified carbon is obtained after drying and solidification.
[0047] Preparation Example 4
[0048] This preparation example is used to prepare modified carbon. Activated carbon is used as a raw material. 5 parts by weight of quaternary ammonium salt is added with water to prepare a solution. 60 parts by weight of activated carbon are immersed in the solution. 35 parts by weight of attapulgite are added. The mixture is stirred and mixed evenly. The modified carbon is obtained after drying and solidification.
[0049] Preparation Example 5
[0050] This preparation example is used to prepare modified carbon. Activated carbon is used as a raw material. 10 parts by weight of quaternary ammonium salt is added with water to prepare a solution. 60 parts by weight of activated carbon are immersed in the solution. 30 parts by weight of attapulgite is added. The mixture is stirred and mixed evenly. The modified carbon is obtained after drying and solidification.
[0051] Examples 1 to 7 are used to prepare natural fiber modified materials, and the details are as follows.
[0052] Example 1
[0053] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0054] 5 parts by weight of hemp fiber are uniformly mixed with 12 parts by weight of activated carbon, 1 part by weight of a silane coupling agent, 5 parts by weight of a fire retardant, 1 part by weight of a waterproofing agent and 70 parts by weight of polystyrene resin beads to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 minutes to obtain a natural fiber modified material.
[0055] Example 2
[0056] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0057] 8 parts by weight of hemp fiber are uniformly mixed with 10 parts by weight of activated carbon, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 72 parts by weight of polystyrene resin beads to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 minutes to obtain a natural fiber modified material.
[0058] Example 3
[0059] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0060] 10 parts by weight of hemp fiber are uniformly mixed with 8 parts by weight of activated carbon, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 75 parts by weight of polystyrene resin beads to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 minutes to obtain a natural fiber modified material.
[0061] Example 4
[0062] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0063] 8 parts by weight of hemp fiber are uniformly mixed with 5 parts by weight of activated carbon, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 78 parts by weight of polystyrene resin beads to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 minutes to obtain a natural fiber modified material.
[0064] Example 5
[0065] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0066] 5 parts by weight of hemp fiber are uniformly mixed with 8 parts by weight of activated carbon, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 80 parts by weight of polystyrene resin beads to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 minutes to obtain a natural fiber modified material.
[0067] Example 6
[0068] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0069] 8 parts by weight of hemp fiber are uniformly mixed with 10 parts by weight of activated carbon, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 82 parts by weight of polystyrene resin beads to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 minutes to obtain a natural fiber modified material.
[0070] Example 7
[0071] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0072] 10 parts by weight of hemp fiber are uniformly mixed with 12 parts by weight of activated carbon, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 85 parts by weight of polystyrene resin beads to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 minutes to obtain a natural fiber modified material.
[0073] The natural fiber modified materials prepared in the above Examples 1 to 7 were prepared into 5 cm thick boards, and the density, thermal conductivity, fire rating, bending strength and sound insulation effect of the boards were tested. The test results are shown in Table 1.
[0074] Table 1
[0075]
[0076] It can be seen from Examples 1 to 7 and Table 1 that the natural fiber modified material prepared by the technical solution of the present application is used in the insulation board, and the board has a low density, a low thermal conductivity, and a fire resistance grade of B. 1 The bending strength can reach 0.38MPa and the sound insulation effect can reach more than 36dB.
[0077] Further analysis of Table 1 shows that the amount of polystyrene resin beads and activated carbon added in the technical solution of the present application has a great influence on the material properties. The inventors believe that the activated carbon filled in the middle of the polystyrene foam material can increase the density by a small amount while improving the thermal insulation performance, sound insulation effect and bending strength of the material, thereby making the performance of the thermal insulation board prepared from the material better.
[0078] In Examples 8 to 14, while keeping other formulas and preparation processes unchanged, the inventors modified the activated carbon as follows.
[0079] Example 8
[0080] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0081] 5 parts by weight of hemp fiber, 12 parts by weight of modified carbon prepared in Preparation Example 1, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 70 parts by weight of polystyrene resin beads are uniformly mixed to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 min to obtain a natural fiber modified material.
[0082] Example 9
[0083] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0084] 8 parts by weight of hemp fiber, 10 parts by weight of modified carbon prepared in Preparation Example 2, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 72 parts by weight of polystyrene resin beads are uniformly mixed to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 min to obtain a natural fiber modified material.
[0085] Example 10
[0086] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0087] 10 parts by weight of hemp fiber, 8 parts by weight of modified carbon prepared in Preparation Example 3, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 75 parts by weight of polystyrene resin beads are uniformly mixed to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 min to obtain a natural fiber modified material.
[0088] Embodiment 11
[0089] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0090] 8 parts by weight of hemp fiber, 5 parts by weight of modified carbon prepared in Preparation Example 4, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 78 parts by weight of polystyrene resin beads are uniformly mixed to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 min to obtain a natural fiber modified material.
[0091] Example 2
[0092] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0093] 5 parts by weight of hemp fiber, 8 parts by weight of modified carbon prepared in Preparation Example 5, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 80 parts by weight of polystyrene resin beads are uniformly mixed to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 min to obtain a natural fiber modified material.
[0094] Embodiment 13
[0095] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0096] 8 parts by weight of hemp fiber, 10 parts by weight of modified carbon prepared in Preparation Example 3, 1 part by weight of silane coupling agent, 5 parts by weight of fire retardant, 1 part by weight of waterproofing agent and 82 parts by weight of polystyrene resin beads are uniformly mixed to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 min to obtain a natural fiber modified material.
[0097] Embodiment 14
[0098] In this embodiment, the hemp fibers are first cleaned, dried, and cut into small segments of 5 to 10 mm;
[0099] 10 parts by weight of hemp fiber, 12 parts by weight of modified carbon prepared in Preparation Example 1, 1 part by weight of a silane coupling agent, 5 parts by weight of a fire retardant, 1 part by weight of a waterproofing agent, and 85 parts by weight of polystyrene resin beads are uniformly mixed to obtain a mixture; the mixture is hot-pressed at a temperature of 120° C. for 18 min to obtain a natural fiber modified material.
[0100] The natural fiber modified materials prepared in the above Examples 8 to 14 were prepared into 5 cm thick boards, and the density, thermal conductivity, fire rating, bending strength and sound insulation effect of the boards were tested. The test results are shown in Table 2.
[0101] Table 2
[0102]
[0103]
[0104] It can be seen from Examples 8 to 14 and Table 2 that, based on the technical solution of the present application, the performance of the prepared thermal insulation board can be further improved by replacing the activated carbon with the modified carbon prepared in Preparation Examples 1 to 5; the density and thermal conductivity of the thermal insulation board do not increase significantly, but the fire resistance grade can reach A, the bending strength can reach above 0.42 MPa, and the sound insulation effect is further improved, reaching above 38 dB. This indicates that the modified carbon with attapulgite added can further improve the fire resistance of the material, and the bending strength is significantly improved.
[0105] Examples 15 to 21 are based on Examples 8 to 14, with only the preparation process changed. The polystyrene resin beads are first pre-foamed by heating at a foaming temperature of 80°C for 3 min; then they are mixed evenly with hemp fiber, modified carbon, silane coupling agent, fire retardant and waterproofing agent and then aged at a temperature of 40°C for 3 h; subsequently, hot pressing is performed at a temperature of 120°C for 10 min to obtain a natural fiber modified material.
[0106] The natural fiber modified materials prepared in the above Examples 15 to 21 were prepared into 5 cm thick boards, and the density, thermal conductivity, fire rating, bending strength and sound insulation effect of the boards were tested. The test results are shown in Table 3.
[0107] Table 3
[0108]
[0109]
[0110] It can be seen from Examples 15 to 21 and Table 3 that, on the basis of the technical solution of the present application, the polystyrene resin beads are pre-foamed, and the pre-foamed polystyrene is evenly mixed with other components, so that the hemp fiber can be more easily connected to a plurality of different polystyrene resin beads, so that the connection performance of the polystyrene after foaming is higher, thereby improving the bending strength; and the modified carbon particles can better enter the interior of the polystyrene and be wrapped by the polystyrene, thereby improving the fire resistance level and sound insulation effect.
[0111] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A natural fiber modified material, characterized in that: The invention is prepared by comprising the following components in parts by weight: 70-85 parts of polystyrene resin beads; 5-10 parts of hemp fiber; 5-12 parts of modified carbon; Silane coupling agent 0.5-2 parts; 5-8 parts of fire retardant; 1 to 3 parts of waterproofing agent; The modified carbon uses activated carbon as a raw material, the activated carbon is impregnated in quaternary ammonium salt, attapulgite is added, the mixture is stirred and evenly mixed, and the modified carbon is obtained after drying and solidification.
2. The natural fiber modified material according to claim 1, characterized in that: The modified carbon is prepared under acidic conditions.
3. The natural fiber modified material according to claim 1, characterized in that: In the modified carbon, the weight ratio of activated carbon, quaternary ammonium salt and attapulgite is (50-60):(5-10):(30-40).
4. The natural fiber modified material according to claim 1, characterized in that: The particle size of the activated carbon is 0.5 to 5 mm; And / or, the particle size of the attapulgite is 0.2 to 1 μm.
5. The natural fiber modified material according to claim 1, characterized in that: The fire retardant is one or more combinations of ammonium phosphate and zinc borate.
6. The natural fiber modified material according to claim 1, characterized in that: The waterproofing agent is an organic silicon emulsion, and polyethylene glycol 800 is added to the organic silicon emulsion.
7. A method for preparing the natural fiber modified material according to claim 1, characterized in that: The following steps are involved: S1. Washing, drying and cutting the hemp fibers into segments; S2, mixing the pretreated hemp fiber in S1 with the modified carbon, the silane coupling agent, the fire retardant, the waterproof agent and the polystyrene resin beads to obtain a mixture; S3, hot pressing the mixture in S2 to obtain a natural fiber modified material.
8. The preparation method according to claim 7, characterized in that: The length of the hemp fiber after being cut into segments is 5 to 10 mm.
9. The preparation method according to claim 7, characterized in that: The polystyrene resin beads in S2 are first pre-foamed by heating, and then mixed evenly with the hemp fibers pretreated in S1, the modified carbon, the silane coupling agent, the fire retardant and the waterproof agent, and then aged to obtain a mixture.
10. Use of the natural fiber modified material according to claim 1 in the field of building thermal insulation.